Prolonged QTc-Interval in Liver Cirrhotic Patient: Prevalence and Its Relationship with Severity of Liver Dysfunction - Iman Firmansyah; Irsan Hasan; Laurentius Lesmana; Idrus Alwi; Pudji Rahardjo (The Indonesian Society for Digestive Endoscopy, 2004)
Background: The aim of the study was to determine the prevalence of prolonged QTc -interval and it’s relationship with the severity of liver dysfunction in liver cirrhotic patient in the outpatient clinic of Hepatology, Dr. Cipto Mangunkusumo General National Hospital Methods: cross sectional study. Eighty one subjects was recruited and being followed as a consecutive non random sampling. The patient was divided according to the modified Child-Pugh classification and undergo to the ECG examination (with minimal 2 leads have measured QT-interval; one of these is II, aVL, V2 or V3 lead). Result: The prolonged QTc-interval prevalence in liver cirrhotic patient was found in 55 subjects (67,9%) with the mean 448.6 msec (SD = 28,9; 95% CI = 442.2 - 454.8). Using the Forward Stepwise Method in multivariate analysis to the independent variables (p 0.05) was found only the modified Child-Pugh classification had strongly correlation with the prolonged QTc-interval (OR = 11.2; 95% CI = 3.57-35.47; p = 0.000) Conclusion: The prolonged QTc-interval prevalence in liver cirrhotic patient is 67.9%. The prolonged QTc-interval were strongly associated with the severity of liver dysfunction. Keywords: The prolonged QTc-interval, liver dysfunction, liver cirrhosis